Familial café au lait spots: a variant of neurofibromatosis type 1. Issue 12 (December 1995) - Abeliovich, D; Gelman-Kohan, Z; Silverstein, S; Lerer, I; Chemke, J; Merin, S; Zlotogora, J
Abstract : Café au lait spots (CALS) are a frequent and one of the early manifestations of neurofibromatosis 1 (NF1). However, there are patients with isolated CALS who do not meet the diagnostic criteria for NFI. There are several reports of families in which CALS are inherited as an autosomal dominant trait, without any other features of NFI. In one reported family with dominantly inherited CALS linkage to the NF1 locus was ruled out. In order to elucidate the relationship between familial CALS and NF1 further, we performed a linkage analysis in a large kindred with 11 subjects with CALS in three generations and established close linkage between CALS and five NF1 intragenic polymorphisms. We propose that in this family the trait of CALS is allelic to NF1, it is fully penetrant, and it does not confer a risk of other NF1 symptoms.